Polyhydramnios associated with rare genetic syndromes: two case reports - C. W. C. Lim; I. E. Lustestica; W. B. Poon; W. C. Tan (Journal of Medical Case Reports, 2024)
Abstract Background We present two genetic causes of polyhydramnios that were challenging to diagnose due to their rarity and complexity. In view of the severe implications, we wish to highlight these rare genetic conditions when obstetricians consider differential diagnoses of polyhydramnios in the third trimester. Case presentation Patient 1 is a 34-year-old Asian woman who was diagnosed with polyhydramnios at 28 weeks’ gestation. First trimester testing, fetal anomaly scan, and intrauterine infection screen were normal. Subsequent antenatal ultrasound scans revealed macroglossia, raising the suspicion for Beckwith–Wiedemann syndrome. Chromosomal microarray analysis revealed a female profile with no pathological copy number variants. The patient underwent amnioreduction twice in the pregnancy. The patient presented in preterm labor at 34 weeks’ gestation but elected for an emergency caesarean section. Postnatally, the baby was noted to have a bell-shaped thorax, coat hanger ribs, hypotonia, abdominal distension, and facial dysmorphisms suggestive of Kagami–Ogata syndrome. Patient 2 is a 30-year-old Asian woman who was diagnosed with polyhydramnios at 30 weeks’ gestation. She had a high-risk first trimester screen but declined invasive testing; non-invasive prenatal testing was low risk. Ultrasound examination revealed a macrosomic fetus with grade 1 echogenic bowels but no other abnormalities. Intrauterine infection screen was negative, and there was no sonographic evidence of fetal anemia. She had spontaneous rupture of membranes at 37 + 3 weeks but subsequently delivered by caesarean section in view of pathological cardiotocography. The baby was noted to have inspiratory stridor, hypotonia, low-set ears, and bilateral toe polysyndactyly. Further genetic testing revealed a female profile with a pathogenic variant of the GLI3 gene, confirming a diagnosis of Greig cephalopolysyndactyly syndrome. Conclusion These cases illustrate the importance of considering rare genetic causes of polyhydramnios in the differential diagnosis, particularly when fetal anomalies are not apparent at the 20-week structural scan. We would like to raise awareness for these rare conditions, as a high index of suspicion enables appropriate counseling, prenatal testing, and timely referral to pediatricians and geneticists. Early identification and diagnosis allow planning of perinatal care and birth in a tertiary center managed by a multidisciplinary team.